Formation of palladium nano-gap on self-cracked WO3 for hydrogen gas sensors. (8th January 2023) - Kim, Noeul; Cho, Hyeon Ho; Kim, Youngho; Hwang, Jongkook; Choi, Jae-Young; Yu, Hak Ki
Abstract: In the event of a hydrogen leak accident, an explosion occurs at a concentration of 4% or more in the atmosphere, so, the technology to accurately measure the hydrogen detection near the 5% area is very important. Among the various hydrogen detection methods, a hydrogen sensor using a fine pattern of Pd with excellent ability to absorb hydrogen is very suitable for this purpose. In this study, in forming a micropattern of Pd metal, a technique for easily fabricating Pd micropatterns was proposed by utilizing micro-cracks generated in the process of forming a ceramic thin film on a polymer substrate. It showed very accurate detection capability at the 1–5% hydrogen concentration level, and it is expected that it can be easily applied to various curvature environments as it is manufactured on a polymer substrate. Highlights: Pd micropatterns by utilizing micro-cracks generated during forming a ceramic thin film on a polymer substrate. Accurate detection capability at the 1–5% hydrogen concentration level. Can be applied to various curvature environments as it is manufactured on a polymer substrate.